Associations of dietary selenium intake with the risk of chronic diseases and mortality in US adults - Zhang, Yuchen; Meng, Shixin; Yu, Yuexin; Bi, Liangwen; Tian, Jihong; Zhang, Lizhen (Frontiers in Nutrition, 2024)
Objective: Selenium is an essential micronutrient and a type of dietary antioxidant.This study aimed to investigate the associations of dietary selenium intake with the risk of human chronic disease (cardiovascular disease (CVD), diabetes mellitus (DM), and cancer) and mortality among US general adults.Methods: The dietary and demographic data in this study were collected from the National Health and Nutrition Examination Survey (NHANES) from 2007 to 2018. Death outcomes were determined by associating with the National Death Index (NDI) records as of December 31, 2019. Logistic regression analyses were used to investigate the relationship of selenium intake with the risk of CVD, DM, and cancer.The effect of dietary selenium on all-cause and disease-specific mortality was estimated with restricted cubic spline (RCS) curves based on the univariate and multivariate Cox proportional hazard models.Results: Among the 25,801 participants, dietary selenium intake was divided into quintiles (Q1-Q5). After covariate adjustment, the results showed that the participants with higher quintiles (Q4 and Q5) of selenium intake tended to have a low risk of CVD (OR=0.97, 95%CI: 0.96, 0.99; OR=0.98, 95%CI: 0.97, 1.00, respectively). Moreover, the RCS curves showed a significant nonlinear association between selenium intake and the risk of all-cause (with a HR of 0.82, 95%CI: 0.68, 0.99) and DM-specific mortality (with the lowest HR of 0.30; 95% CI, 0.12-0.75). Furthermore, we conducted a subgroup analysis and found a negative correlation between the highest quartile of selenium intake and all-cause mortality among participants aged 50 and above (HR=0.75, 95% CI: 0.60-0.93, P=0.009). Conclusion: Our results indicated that a moderate dietary selenium supplement decreased the risk of CVD and displayed a nonlinear trend in association with the risk of all-cause and DM-specific mortality among US adults. In addition, we found that participants aged 50 and older may benefit from higher selenium intake. However, these findings still need to be confirmed through further mechanism exploration.